Perilaku Komunikasi Internal Pengguna Game Online Di Masa Pandemi Covid-19 - Mirwan Hariri; Miftakhul Rohman (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2022)
Abstract The condition of the Covid-19 pandemic in Blitar Regency has an impact on the behavior of children and students. Where before the pandemic their routine from morning to afternoon/evening was at school, but during the pandemic conditions they were only at home, school activities were carried out online from home. The process of learning school material is only done for a few hours, not in accordance with school hours in general, and the rest they do is play online games at home. Interpersonal communication that takes place between online game users in a team aims to achieve common goals within the scope of the game, both individually and in groups. The purpose of this study was to analyze the interpersonal communication behavior of online game users during the Covid-19 pandemic, a case study in Bangle Village, Kec. Kanigoro Kab. Blitar. This study also aims to determine the relationship between the quality of interpersonal communication of online game users during the covid-19 pandemic in Bangle Village, sub-district. Kanigoro kab. Blitar. This type of research is qualitative by describing a result of research and efforts to find phenomena regarding an event. Analyze and conduct in-depth data mining thoroughly on what is happening in it. The conclusion of this study is that the interpersonal communication behavior of online game users is stingy, selfish, optimistic, and uses harsh words that should not be spoken either when playing online games or in everyday life. As well as online game users in their teens, they also have unstable lives, such as: lack of rest patterns, eating patterns, and lack of interaction with the surrounding environment. In interacting while playing online games together, teenagers still adhere to health protocols. Keywords: Interpersonal Communication, Online Games, Covid-19 Pandemic